FOREIGN LEARNERS’ PERCEPTION, SATISFACTION, AND LEARNING OUTCOME IN LEARNING INDONESIAN LANGUAGE - Imam Suyitno; Kusubakti Andayani; Peni Dyah Anggari; Taufiq Kurniawan; Heni Dwi Arista (Jurnal Cakrawala Pendidikan, 2021)
Indonesian language learning institute for foreign learners emphasizes on increasing the experiences and skills of foreigners to speak Indonesian in the real context. One of the models used to achieve this is by optimizing the learning process. Therefore, this research studied the learning model and its impact on the perceptions, satisfaction, and outcomes using qualitative and quantitative approaches. The sample study consists of 21 foreign learners and 10 tutors. Data were obtained from the experiential-tutorial learning, scores of perception, satisfaction, and outcomes through interviews, questionnaires, and tutor assessment on the speaking abilities recorded on document sheets. The study found that the experiential-tutorial learning was developed based on the learners’ daily communication needs. The statistical analysis results showed that the average scores of their perception, satisfaction, and learning outcomes were in the high category. Therefore, foreign learners have a good perception and high learning satisfaction in conducting experiential-tutorial learning to increase their outcomes. These findings indicate that experiential-tutorial learning is an effective model for foreign language learners.